Links Between the Phytoplankton Community Composition and Trace Metal Distribution in Summer Surface Waters of the Atlantic Southern Ocean - Viljoen, Johannes J.; Weir, Ian; Fietz, Susanne; Cloete, Ryan; Loock, Jean; Philibert, Raissa; Roychoudhury, Alakendra N. (Frontiers in Marine Science, 2019)
This study assessed changes in the phytoplankton community related to macronutrient and bioactive trace metal distribution in surface waters of the Atlantic sector of the Southern Ocean, between Cape Town and Antarctica along the GEOTRACES GIPY_05 (mainly along prime meridian) transect in summer 2014-2015. Several general community structure features were reaffirmed, such as the restriction of cyanobacteria to the northern Subtropical Zone, while haptophytes, such as Phaeocystis, along with diatoms, dominate the community north of the Polar Front, and diatoms clearly dominate south of the Polar Front. These community structure changes were often linked with macro- and micronutrient composition changes. For example, the concentration of diatoms increased southwards with the availability of silica whereas the cyanobacterial contribution in the northern Subtropical Zone appeared to be linked with labile cobalt depletion. However, these links were not consistent along the entire transect, i.e. no individual nutrient, such as silica or iron, was linked to community composition changes across all water masses. Each station showed a rather unique combination of nutrient and community compositions. Our findings also indicated impacts on the phytoplankton community through trace metal distributions that could be related to a deep mixing event at ~54 °S and to ice melt at ~65 °S and 68 °S. The timing of sampling after such trace metal fluxes proved to be an important consideration, particularly where iron appeared to be preferentially depleted to near-limiting concentrations, possibly driving utilization of other metals. The study highlights the importance of considering a suite of trace metals when assessing controls of phytoplankton variability in the open ocean and emphasises the need for higher resolution trace metal sampling and multi-element incubation studies to further study the complex relationships between phytoplankton and nutrients.